Microbiological Profile and Hygienic Quality of Foodstuffs Marketed in Collective Catering in Central Morocco - Rachid Amaiach; Sanae Lairini; Mouhcine Fadil; Moussa Benboubker; Rabia Bouslamti; Soukaina El Amrani; Abdelhakim El Ouali Lalami (International Journal of Food Science)
Food hygiene is important both for its impact on the health of citizens and also for the cost of the infections that it can generate. In Morocco, it has become a concern of authorities. This work, realized for the first time in the center of Morocco, is aimed at describing the microbiological quality of foodstuffs marketed in collective catering in central Morocco. This study was conducted retrospectively from January 2015 to December 2019 in Fez city, central Morocco. The samples collected by the competent authority during official control from restaurants and food outlets were analyzed. Non-conformity was chosen as an indicator of food quality according to the official Moroccan standards. The samples were presented according to several variables: year/month/season, category/subcategory, communes, and establishment. The statistical processing of the results was done by SPSS 25. The Chi2 statistical test was calculated to determine a relationship between non-conformity and the type of analyzed matrix (year, season, and food category). The test was considered statistically significant for a p value < 0.05. A total of 2223 food samples were investigated, with an annual average of 445 samples. Overall, the rate of non-compliance during 2015-2019 was 31%, reaching its maximum in 2017 (36.4%) and its minimum in 2018 (27.5%).This rate varies by food type. Juices/drinks and meat products are the most contaminated with 71.7% and 58.1%, respectively, followed by milk and derivatives with 43.2%, seasoning sauces with 28.6%, pastries and pastry creams with 21.4%, and 14.4% for ready meals. The main causes of food non-conformity were fecal contamination germs with 67% positive fecal coliforms and 15% of total coliforms followed by total germs (7%), Staphylococcus aureus (5%), yeasts and molds (3%), sulfite-reducing anaerobes (2%), and Salmonella (1%). Given the obtained results, improving the hygienic quality of foods is necessary to ensure better consumer safety.